2018
DOI: 10.1097/icl.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Overnight Orthokeratology on Corneal Sub-basal Nerve Plexus Morphology and Corneal Sensitivity

Abstract: Objective: To assess the effects of a short period of orthokeratology (OK) on corneal subbasal nerve plexus (SBNP) morphology and corneal sensitivity. Methods: Measurements were made in 56 right eyes of 56 subjects with low-to-moderate myopia who wore 2 OK lens designs (Group CRT: HDS 100 Paragon CRT, n¼35; Group SF: Seefree; n¼21) for a period of 1 month and in 15 right eyes of noncontact lens wearers as controls. The variables determined in each participant were corneal sensitivity using a Cochet-Bonnet esth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
4
15
1
Order By: Relevance
“…Using this technology, it has being possible to assess these changes in the corneas of healthy individuals 10 , soft contact lens wearers 7,8 , subjects undergoing corneal surgery 12,13 , patients with a systemic diseass 14,15 and those undergoing overnight orthokeratology (OK) treatment 9,16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this technology, it has being possible to assess these changes in the corneas of healthy individuals 10 , soft contact lens wearers 7,8 , subjects undergoing corneal surgery 12,13 , patients with a systemic diseass 14,15 and those undergoing overnight orthokeratology (OK) treatment 9,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…SBNP nerve redistribution has been linked to increased levels of pro-inflammatory molecules 22 . Consequently, and bearing in mind that inflammation due to the use of contact lenses induces the migration of Langerhans cells (LC) to the cornea 23,24 , we recently performed a study 17 in which it was observed that the use of OK lenses over a short period increases LC density in the cornea. However, little is still known about the course of these changes in the longer term and their possible recovery after interrupting OK lens wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that lasik refractive surgery in myopia alters the nerve plexus by reducing its density over a period of time . New information also suggests orthokeratology can cause changes to the density of the nerve bed . Some groups have documented that density decreases with age .…”
Section: Introductionmentioning
confidence: 99%
“…3 New information also suggests orthokeratology can cause changes to the density of the nerve bed. 4 Some groups have documented that density decreases with age. [5][6][7][8] To our knowledge, no research groups thus far have examined changes in nerve density specifically for patients of different refractive errors.…”
Section: Introductionmentioning
confidence: 99%